Akrotiri Thera : an architecture of affluence 3,500 years old - Palybu, Klairē (Prehistory monographs, 2005)
1.The volcanic fate of Thera --2.The archaeologist : an unexpected visitor 3,500 years later --3.The settlement pattern of Thera during the 2nd millennium B.C. --4.The Akrotiri region : landscape, past and present --5.The town --6.The buildings --7.A guided tour through the town --8.A synopsis of the Theran house model --9.The art of building : materials and techniques --10.Design and morphology --11.Reconciling with the wrath of Engelados --12.Thera and her neighbors in a time of opulence.